Decorative panels

The use of a crystalline polyester polyol-based adhesive in decorative boards ensures strong adhesion between base materials and decorative sheets, addressing peeling issues and improving construction efficiency.

JP7608039B2Active Publication Date: 2025-01-06DIC CORP

Patent Information

Application Number
JP2018212169
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-11-12
Publication Date
2025-01-06
Estimated Expiration
2038-11-12

AI Technical Summary

Technical Problem

Decorative sheets used in architectural materials face issues with insufficient adhesion in grooves, leading to lifting or peeling, which affects productivity and construction time.

Method used

A decorative board is created by bonding a base material and decorative sheet using a moisture-curable polyurethane hot melt adhesive with a urethane prepolymer derived from a specific crystalline polyester polyol and polyisocyanate, ensuring continuous bonding to the side and flat surfaces, including grooves.

Benefits of technology

The solution provides excellent initial and final adhesion, preventing lifting or peeling of decorative sheets, even in grooved base materials, enhancing productivity and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608039000001
    Figure 0007608039000001
  • Figure 0007608039000002
    Figure 0007608039000002
  • Figure 0007608039000003
    Figure 0007608039000003
Patent Text Reader

Abstract

To provide a decorative laminate excellent not only in initial adhesiveness between a substrate and a decorative sheet, but also in final adhesiveness without occurrence of floating and peeling of the decorative sheet even in the case of having a groove part.SOLUTION: A decorative laminate includes a substrate and a decorative sheet, which are laminated through an adhesive. To a side part and a plane surface part of the substrate, the decorative sheet is continuously laminated. The adhesive is made from crystalline polyester polyol (a1-1) having a melting point of more than 80°C and 140°C or less as raw material. The amount of the crystalline polyester polyol (a1-1) used is in the range of 5 to 45 parts by mass in 100 parts by mass of a polyol (a) and a polyisocyanate (b) in total.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a decorative board. [Background technology]

[0002] Decorative boards, in which a decorative sheet is bonded to a plate-shaped substrate, are widely used for architectural interior materials such as flooring, doors, fixtures, tabletops, etc. For the decorative boards used for flooring, for example, a method in which a decorative sheet is bonded to each substrate, and the resulting substrates are then joined together without gaps one by one to create a flooring material is widely used.

[0003] However, it has been pointed out that this method results in a lot of wastage of the decorative sheet because the decorative sheet is attached to each base material, and the construction time is long, resulting in low productivity.Instead, in recent years, a method has been considered in which a groove is provided in a large-area base material, and a decorative sheet is attached integrally from above using vacuum lamination or the like to produce a large-area flooring material (see, for example, Patent Document 1).

[0004] Known examples of adhesives that can be used in the above-mentioned processing include moisture-curable polyurethane hot melt adhesives that contain a urethane prepolymer having an isocyanate group obtained by reacting a polyol containing an alicyclic polyester polyol and an aliphatic polyester polyol with 4,4'-diphenylmethane diisocyanate (see, for example, Patent Document 2).

[0005] However, the moisture-curing polyurethane hot melt adhesive has the problem that adhesion of the decorative sheet is insufficient in the grooves of the base material, causing the decorative sheet to lift or peel off. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2004-74657 A [Patent Document 2] JP 2013-87150 A Summary of the Invention [Problem to be solved by the invention]

[0007] The problem to be solved by the present invention is to provide a decorative board having excellent initial adhesion between the substrate and the decorative sheet, and also having excellent final adhesion that prevents lifting or peeling of the decorative sheet. [Means for solving the problem]

[0008] The present invention provides a decorative board in which a substrate and a decorative sheet are bonded together via an adhesive, the decorative sheet being continuously bonded to the side and flat portions of the substrate, the adhesive being a moisture-curing polyurethane hot melt adhesive containing a urethane prepolymer having an isocyanate group, which is a reaction product of polyol (a) and polyisocyanate (b), and the polyol (a) containing a crystalline polyester polyol (a1-1) having a melting point exceeding 80°C and not exceeding 140°C. Effect of the Invention

[0009] The decorative board of the present invention has excellent initial adhesion between the substrate and the decorative sheet, and also has excellent final adhesion without lifting or peeling of the decorative sheet. In particular, even when a substrate having a groove is used, adhesion can be imparted to the substrate without lifting or peeling of the decorative sheet even in the groove.

[0010] Therefore, the decorative board of the present invention can be suitably used for flooring materials; doors such as shoe door doors, closet doors, kitchen doors, etc.; construction materials such as frames, picture frames, baseboards, etc.; counter table tops, furniture tops, etc.; and is particularly suitable for use as a flooring material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The decorative board of the present invention is formed by bonding a base material and a decorative sheet together via a specific adhesive, and the base material has grooves on its planar surface in the longitudinal direction and in at least one direction other than the longitudinal direction, and the decorative sheet is continuously bonded to the side surface, planar surface, and grooves provided on the planar surface of the base material.

[0012] Examples of the substrate that can be used include wood substrates such as plank-shaped wood, laminated lumber, plywood, MDF (medium density fiberboard), and particle board; and inorganic substrates such as hard cement calcium silicate board.

[0013] The thickness, width, and length of the substrate are each appropriately determined depending on the application of the decorative board, and examples of such ranges include a length of 600 to 4,000 mm, a width of 50 to 5,000 mm, and a thickness of 2 to 18 mm.

[0014] The substrate may be either one having grooves or one not having grooves. When the substrate has grooves, the substrate may have grooves in its longitudinal direction (the direction in which the width is longer. If the width is the same in both the vertical and horizontal directions, one of the two directions is indicated) and at least one direction other than the longitudinal direction. There may be one groove or two or more grooves in the longitudinal direction, and there may be one groove or two or more grooves in the direction other than the longitudinal direction. The direction of the grooves other than the longitudinal direction is preferably perpendicular to the longitudinal direction, since this is the most frequently used direction and it is easy to make the decorative sheet follow the grooves in the line production.

[0015] The grooves of the substrate include cylindrical grooves, triangular grooves, flat grooves, dovetail grooves, etc. These grooves may be one type or two or more types mixed together. Among these, triangular grooves are preferred because they are frequently used in flooring materials and have good conformity to the grooves of the decorative sheet.

[0016] The depth of the groove is appropriately determined depending on the application of the decorative board, but may be, for example, in the range of 0.5 to 3 mm, and the width of the groove may be, for example, in the range of 0.5 to 3 mm.

[0017] The decorative sheet that can be used in the present invention may be plain or may have a decorative color or pattern. The material of the decorative sheet may be, for example, polyvinyl chloride, polyolefin, polymethylmethacrylate, polyester, polyamide, polystyrene, polycarbonate, ethylene-vinyl acetate copolymer, polyvinyl alcohol, polyethylene, polypropylene, or other resin; decorative paper, nonwoven fabric, woven fabric, thin wood veneer, tatami mat surface, etc. Among these, it is preferable to use polyvinyl chloride, polyolefin, polymethylmethacrylate, or polyester from the viewpoint of conformability to grooves.

[0018] The thickness of the decorative sheet is preferably in the range of 0.05 to 0.3 mm, and more preferably in the range of 0.1 to 0.2 mm, in view of excellent conformability to the grooves.

[0019] The substrate and the decorative sheet are bonded together using a specific adhesive, which will be described later. The thickness of the adhesive layer can be appropriately determined as long as sufficient adhesion is obtained, and may be, for example, in the range of 0.03 to 0.15 mm.

[0020] The decorative plate of the present invention is a laminate of the above-mentioned substrate and decorative sheet, the decorative sheet being continuously laminated to the side and flat surfaces of the substrate, and when the substrate has grooves, the decorative sheet is also laminated to the grooves provided on the flat surface of the substrate. The decorative sheet may also be laminated to the back surface of the substrate (the back side of the flat surface).

[0021] Next, a method for producing the decorative board of the present invention will be described.

[0022] When the substrate does not have a groove, a method for manufacturing the decorative panel can be, for example, a method in which an adhesive is applied onto the decorative sheet and the decorative sheet is bonded to the flat surface, sides, and optionally the back surface of the substrate.

[0023] In addition, the manufacturing method of the decorative board when the substrate has a groove portion can be, for example, a method of applying an adhesive onto the decorative sheet, bonding the decorative sheet to the flat surface, side surface, and sometimes back surface of the substrate having the groove, (i) locally heating the decorative sheet corresponding to the groove portion of the substrate, locally softening the decorative sheet, and pressing it against the groove portion of the substrate; (ii) a method of bonding the substrate and the decorative sheet together by vacuum lamination (hereinafter, abbreviated as "vacuum wrapping molding"). When performing the vacuum lamination, it can be performed while applying heat of, for example, 70 to 140 ° C. Among these, it is preferable to adopt the above-mentioned (ii) because the decorative board can be easily obtained. In the present invention, the above-mentioned (ii) can be preferably adopted by using a specific adhesive described later.

[0024] Next, the adhesive used in the present invention will be described.

[0025] The adhesive is a moisture-curable polyurethane hot melt adhesive containing a urethane prepolymer having an isocyanate group, which is a reaction product of a polyol (a) and a polyisocyanate (b), and it is essential to use a crystalline polyester polyol (a1-1) having a specific melting point as a raw material.

[0026] The crystalline polyester polyol (a1-1) must have a melting point of more than 80° C. and not more than 140° C. to provide excellent adhesion. It is presumed that the use of a crystalline polyester polyol having such a melting point range provides high cohesive strength when the sheet is heated and conformed to the grooves, thereby providing excellent initial adhesion. The melting point of the crystalline polyester polyol (a1-1) is preferably in the range of 85 to 130° C., more preferably in the range of 90 to 120° C., and even more preferably in the range of 95 to 110° C., in order to provide even better initial adhesion.

[0027] The amount of the crystalline polyester polyol (a1-1) used is preferably in the range of 5 to 45 parts by mass, more preferably in the range of 8 to 43 parts by mass, more preferably in the range of 10 to 42 parts by mass, even more preferably in the range of 15 to 41 parts by mass, and particularly preferably in the range of 30 to 40 parts by mass, per 100 parts by mass of the total of the polyol (a) and the polyisocyanate (b), in order to obtain even better initial adhesion and workability.

[0028] Specifically, the crystalline polyester polyol (a1-1) may be, for example, a reaction product of a compound having two or more hydroxyl groups with a polybasic acid.

[0029] Examples of the compound having a hydroxyl group include ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, trimethylolpropane, trimethylolethane, glycerin, neopentyl glycol, and trimethylolpropane. These compounds may be used alone or in combination of two or more. Among these, it is preferable to use one or more compounds selected from the group consisting of butanediol, hexanediol, octanediol, and decanediol, in order to increase crystallinity and further improve initial adhesion.

[0030] Examples of the polybasic acid include oxalic acid, malonic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedicarboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, and phthalic anhydride. These polybasic acids may be used alone or in combination of two or more. Among these, it is preferable to use one or more polybasic acids selected from the group consisting of adipic acid, sebacic acid, dodecanedicarboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, and phthalic anhydride, in order to enhance crystallinity and further improve initial adhesion.

[0031] The melting point of the crystalline polyester polyol (a1-1) correlates with the degree of crystallinity, and it is preferable to use a polyester polyol with high crystallinity. The melting point and crystallinity of the polyester polyol can be adjusted by the selection of raw material monomers, copolymerization composition, average molecular weight, etc. In the present invention, "crystalline" refers to a material in which a peak of heat of crystallization or heat of fusion can be confirmed in a DSC (differential scanning calorimeter) measurement in accordance with JISK7121:2012, and "amorphous" refers to a material in which the peak cannot be confirmed. The method for measuring the melting point of the crystalline polyester polyol (a1-1) will be described in the Examples.

[0032] A preferred composition of the crystalline polyester polyol (a1-1) is a reaction product of hexanediol, sebacic acid, and phthalic acid (one or more selected from the group consisting of isophthalic acid, terephthalic acid, and orthophthalic acid).

[0033] The number average molecular weight of the crystalline polyester polyol (a1-1) is preferably in the range of 500 to 5,000, more preferably in the range of 1,000 to 4,500, and even more preferably in the range of 2,000 to 4,000, in terms of making it easy to adjust the melting point and obtaining even better initial adhesion and workability. The number average molecular weight of the crystalline polyester polyol (a1-1) is a value measured by gel permeation chromatography (GPC).

[0034] The polyol (a) preferably further contains a crystalline polyester polyol (a1-2) having a melting point of 40 to 80° C. By using the (a1-2), both permeability into the substrate and crystallinity can be achieved, and further excellent initial adhesion can be obtained.

[0035] The crystalline polyester polyol (a1-2) can be made from the same raw materials as those used for the (a1-1). Preferably, the compound having two or more hydroxyl groups is one or more compounds selected from the group consisting of ethylene glycol, butanediol, and hexanediol, and the polybasic acid is one or more polybasic acids selected from the group consisting of adipic acid, sebacic acid, and dodecanedicarboxylic acid.

[0036] The method for measuring the melting point of the crystalline polyester polyol (a1-2) is the same as that for the crystalline polyester polyol (a1-1).

[0037] The number average molecular weight of the crystalline polyester polyol (a1-2) is preferably in the range of 500 to 5,000, more preferably in the range of 1,500 to 4,500, and even more preferably in the range of 2,000 to 4,000, in terms of obtaining even better initial adhesion. The number average molecular weight of the crystalline polyester polyol (a1-2) is a value measured by gel permeation chromatography (GPC).

[0038] In addition to the above, the crystalline polyester polyol (a1-2) may be a polycaprolactone polyol. The polycaprolactone polyol may be a reaction product of the above-mentioned compound having two or more hydroxyl groups with ε-caprolactone.

[0039] When a polycaprolactone polyol is used as the (a1-2), the number average molecular weight is preferably in the range of 5,000 to 200,000, more preferably in the range of 10,000 to 150,000, and even more preferably in the range of 30,000 to 100,000, from the viewpoint of further improving the open time and initial adhesion. The number average molecular weight of the polycaprolactone polyol is a value measured by gel permeation chromatography (GPC).

[0040] The total amount of the crystalline polyester polyols (a1-1) and (a1-2) used is preferably 50 parts by mass or more, and more preferably in the range of 50 to 80 parts by mass, per 100 parts by mass of the total of the polyol (a) and the polyisocyanate (b), in order to obtain even better adhesion.

[0041] The polyol (a) may be used in combination with other polyols in addition to the (a1-1) and (a1-2).

[0042] As the other polyol, for example, polyester polyols other than (a1-1) and (a1-2), polyether polyols, polyacrylic polyols, polycarbonate polyols, etc. can be used. These polyols may be used alone or in combination of two or more. Among these, it is preferable to use polyester polyols other than (a1-1) and (a1-2) because they provide even better adhesion. The number average molecular weight of the polyester polyols other than (a1-1) and (a1-2) is preferably in the range of 500 to 10,000. The number average molecular weight of the polyester polyols is a value measured by gel permeation chromatography (GPC).

[0043] Examples of the polyisocyanate (b) include aromatic diisocyanates such as diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate isocyanate, xylylene diisocyanate, phenylene diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate, and aliphatic or alicyclic diisocyanates such as hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and tetramethyl xylylene diisocyanate. (b-1) Diisocyanates such as isocyanurate compounds (b-2) which are monomers of these diisocyanates; adduct compounds; biuret compounds; allophanate compounds; polymethylene polyphenyl polyisocyanate (b-3), etc. These isocyanates may be used alone or in combination of two or more.

[0044] Among the above-mentioned polyisocyanates, the polyisocyanate (b) preferably contains a diisocyanate (b-1) from the viewpoint of good reactivity and adhesiveness, and the diisocyanate (b-1) is preferably an aromatic polyisocyanate, more preferably diphenylmethane diisocyanate. In addition, the polyisocyanate (b) preferably contains an isocyanurate compound (b-2) and / or a polymethylene polyphenyl polyisocyanate (b-3) in addition to the above (b-1) from the viewpoint of obtaining even better final adhesiveness and heat resistance, and more preferably uses (b-2) and (b-3) in combination.

[0045] As the isocyanurate compound (b-2), it is preferable to use an aliphatic isocyanurate compound, since it can provide even better final adhesiveness and heat resistance. When the isocyanurate compound (b-2) is used, the amount of the isocyanurate compound (b-2) used is preferably in the range of 0.1 to 30% by mass, more preferably in the range of 5 to 25% by mass, and even more preferably in the range of 8 to 23% by mass in the polyisocyanate (b).

[0046] The polymethylene polyphenyl polyisocyanate (b-3) is specifically represented by the following formula (2), and preferably, in formula (2), n represents an integer of 1 to 5. TIFF0007608039000001.tif40130 (In formula (2), n is an integer of 1 or more.)

[0047] When the polymethylene polyphenyl polyisocyanate (b-3) is used, the amount of the polymethylene polyphenyl polyisocyanate (b-3) used is preferably in the range of 0.1 to 30 mass %, more preferably in the range of 5 to 25 mass %, and even more preferably in the range of 8 to 23 mass %, in the polyisocyanate (b), in order to obtain even better final adhesiveness and heat resistance.

[0048] The urethane prepolymer is obtained by reacting the polyol (a) with the polyisocyanate (b), and has an isocyanate group that can form a crosslinked structure by reacting with moisture present in the air or in the substrate to which the urethane prepolymer is applied.

[0049] The urethane prepolymer can be produced, for example, by adding a mixture of the polyol (a) dropwise to a reaction vessel containing the polyisocyanate (b), followed by heating and reacting under conditions in which the isocyanate groups of the polyisocyanate (b) are in excess of the hydroxyl groups of the polyol (a).

[0050] In producing the urethane prepolymer, the molar ratio (NCO / OH) of the hydroxyl group in the polyol (a) and the isocyanate group in the polyisocyanate (b) is preferably in the range of 1.5 to 5, more preferably in the range of 1.8 to 3, and even more preferably in the range of 2.2 to 2.6, in order to reduce unreacted polyisocyanate and impart high cohesive strength at high temperatures.

[0051] The isocyanate group content (hereinafter abbreviated as "NCO%") of the urethane prepolymer obtained by the above method is preferably in the range of 1 to 10 mass%, more preferably in the range of 2 to 5 mass%, further preferably in the range of 2.5 to 4.5 mass%, and particularly preferably in the range of 3 to 4.5 mass%, in order to further improve the adhesiveness at high temperatures. The NCO% of the urethane prepolymer is a value measured by potentiometric titration in accordance with JIS K1603-1:2007.

[0052] The moisture-curable polyurethane hot-melt resin composition of the present invention contains the urethane prepolymer, and may contain other additives as required.

[0053] Examples of the other additives that can be used include curing catalysts, antioxidants, tackifiers, plasticizers, light stabilizers, fillers, dyes, pigments, defoamers, fluorescent brighteners, silane coupling agents, waxes, thermoplastic resins, etc. These additives may be used alone or in combination of two or more.

[0054] As described above, the decorative board of the present invention has excellent initial adhesion between the substrate and the decorative sheet, even when a decorative board having grooves is used, and also has excellent final adhesion with no lifting or peeling of the decorative sheet.

[0055] Therefore, the decorative board of the present invention can be suitably used for flooring materials; doors such as shoe door doors, closet doors, kitchen doors, etc.; construction materials such as frames, picture frames, baseboards, etc.; counter table tops, furniture tops, etc.; and is particularly suitable for use as a flooring material. EXAMPLES

[0056] The present invention will now be described in more detail with reference to examples.

[0057] [Example 1] <Preparation of adhesive> Into a four-neck flask equipped with a stirrer, a thermometer, an inert gas inlet, and a reflux condenser, 23 parts by mass of crystalline polyester polyol (a reaction product of hexanediol, terephthalic acid, and sebacic acid, melting point: 100°C, number average molecular weight: 2,000, hereinafter abbreviated as "crystalline PEs-1"), 40 parts by mass of crystalline polyester polyol (a reaction product of hexanediol and dodecanedicarboxylic acid, melting point: 72°C, number average molecular weight: 3,500, hereinafter abbreviated as "crystalline PEs-2"), 40 parts by mass of crystalline polyester polyol (polycaprolactone polyol, A mixture of 10 parts by mass of crystalline PEs-3 (melting point: 50°C, number average molecular weight: 80,000, hereinafter abbreviated as "crystalline PEs-3"), 5 parts by mass of other polyester polyol (a reaction product of ethylene glycol, neopentyl glycol, hexanediol, and adipic acid, number average molecular weight: 5,000, hereinafter abbreviated as "other PEs-1"), and 2 parts by mass of polyoxyethylene polyoxypropylene glycol (number average molecular weight: 4,000, hereinafter abbreviated as "PEt-1") was charged and heated under reduced pressure at 90°C to dehydrate it until the moisture content was 0.05% by mass or less. Next, the temperature inside the reaction vessel was cooled to 60°C, and then 11 parts by mass of diphenylmethane diisocyanate (hereinafter abbreviated as "MDI"), 2 parts by mass of polymethylene polyphenyl polyisocyanate ("Millionate MR-200" manufactured by Tosoh Corporation, hereinafter abbreviated as "Polymeric MDI"), and 3 parts by mass of an isocyanurate compound of hexamethylene diisocyanate (hereinafter abbreviated as "HDI nurate") were added, and the mixture was reacted at 100°C for approximately 3 hours under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a urethane prepolymer. The NCO / OH ratio during production of the resulting urethane prepolymer was 2.39, and the NCO% of the urethane prepolymer was 2.95% by mass.

[0058] <Making decorative panels> The urethane prepolymer was applied to a thickness of 60 μm using a T-die coater on the back of a polyvinyl chloride decorative sheet with a wood grain pattern (thickness 130 μm, softening point 50°C, hereafter abbreviated as "PVC"), and the adhesive layer was bonded only to the flat part of the substrate (MDF 30 cm long, 20 cm wide, 12 mm thick, with a triangular groove (groove width 1 mm, depth 0.8 mm) forming a rectangle 15 cm long and 10 cm wide). Using any 3D vacuum laminator, the pressure was reduced to 0.01 MPa at 110°C and left to stand for 1 minute to perform 3D vacuum wrapping molding, thereby obtaining a decorative board in which the decorative sheet was continuously bonded to the side parts and the groove parts provided in the flat part of the substrate.

[0059] [Example 2] A four-neck flask equipped with a stirrer, thermometer, inert gas inlet, and reflux condenser was charged with 23 parts by mass of crystalline PEs-1, 25 parts by mass of crystalline PEs-2, 10 parts by mass of crystalline PEs-3, 15 parts by mass of crystalline polyester polyol (a reaction of hexanediol and adipic acid, melting point: 58°C, number average molecular weight: 4,500, hereafter abbreviated as "crystalline PEs-4"), 5 parts by mass of other PEs-1, and 2 parts by mass of PEt-1, and heated under reduced pressure at 90°C to dehydrate until the moisture content was 0.05% by mass or less. Next, after cooling the temperature inside the reaction vessel to 60°C, 11 parts by mass of MDI, 2 parts by mass of polymeric MDI, and 3 parts by mass of HDI nurate were added, and the temperature was raised to 110°C. The mixture was reacted for about 3 hours until the isocyanate group content became constant, and then reacted at 100°C for about 3 hours under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a urethane prepolymer. The NCO / OH ratio during production of the resulting urethane prepolymer was 2.49, and the NCO% of the urethane prepolymer was 3.03% by mass. Using this urethane prepolymer, a decorative board was obtained in the same manner as in Example 1.

[0060] [Example 3] A four-neck flask equipped with a stirrer, thermometer, inert gas inlet, and reflux condenser was charged with 30 parts by mass of crystalline PEs-1, 30 parts by mass of crystalline PEs-2, 10 parts by mass of crystalline PEs-3, 10 parts by mass of other PEs-1, and 2 parts by mass of PEt-1, and heated under reduced pressure at 90°C to dehydrate until the moisture content was 0.05% by mass or less. Next, after cooling the temperature inside the reaction vessel to 60°C, 13 parts by mass of MDI, 2 parts by mass of polymeric MDI, and 3 parts by mass of HDI nurate were added, and the temperature was raised to 110°C. The mixture was reacted for about 3 hours until the isocyanate group content became constant, and then reacted at 100°C for about 3 hours under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a urethane prepolymer. The NCO / OH ratio during production of the resulting urethane prepolymer was 2.62, and the NCO% of the urethane prepolymer was 3.55% by mass. Using this urethane prepolymer, a decorative board was obtained in the same manner as in Example 1.

[0061] [Example 4] A four-neck flask equipped with a stirrer, thermometer, inert gas inlet, and reflux condenser was charged with 42 parts by mass of crystalline PEs-1, 20 parts by mass of crystalline PEs-2, 10 parts by mass of crystalline PEs-3, 10 parts by mass of other PEs-1, and 2 parts by mass of PEt-1, and heated under reduced pressure at 90°C to dehydrate until the moisture content was 0.05% by mass or less. Next, after cooling the temperature inside the reaction vessel to 60°C, 19 parts by mass of MDI, 2 parts by mass of polymeric MDI, and 3 parts by mass of HDI nurate were added, and the temperature was raised to 110°C. The mixture was reacted for about 3 hours until the isocyanate group content became constant, and then reacted at 100°C for about 3 hours under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a urethane prepolymer. The NCO / OH ratio during production of the resulting urethane prepolymer was 2.07, and the NCO% of the urethane prepolymer was 2.61% by mass. Using this urethane prepolymer, a decorative board was obtained in the same manner as in Example 1.

[0062] [Example 5] A four-neck flask equipped with a stirrer, thermometer, inert gas inlet, and reflux condenser was charged with 42 parts by mass of crystalline PEs-1, 10 parts by mass of crystalline PEs-2, 10 parts by mass of crystalline PEs-3, 10 parts by mass of crystalline PEs-4, 10 parts by mass of other PEs-1, and 2 parts by mass of PEt-1, and heated under reduced pressure at 90°C to dehydrate until the moisture content was 0.05% by mass or less. Next, after cooling the temperature inside the reaction vessel to 60°C, 11 parts by mass of MDI, 2 parts by mass of polymeric MDI, and 3 parts by mass of HDI nurate were added, and the temperature was raised to 110°C. The mixture was reacted for about 3 hours until the isocyanate group content became constant, and then reacted at 100°C for about 3 hours under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a urethane prepolymer. The NCO / OH ratio during production of the resulting urethane prepolymer was 2.11, and the NCO% of the urethane prepolymer was 2.67% by mass. Using this urethane prepolymer, a decorative board was obtained in the same manner as in Example 1.

[0063] [Example 6] A four-neck flask equipped with a stirrer, thermometer, inert gas inlet, and reflux condenser was charged with 42 parts by mass of crystalline polyester polyol (a reaction of hexanediol, terephthalic acid, and adipic acid, melting point: 96°C, number average molecular weight: 3,500, hereafter abbreviated as "crystalline PEs-5"), 23 parts by mass of crystalline PEs-2, 10 parts by mass of crystalline PEs-3, 10 parts by mass of other PEs-1, and 2 parts by mass of PEt-1, and heated under reduced pressure at 90°C to dehydrate until the moisture content was 0.05% by mass or less. Next, after cooling the temperature inside the reaction vessel to 60°C, 8 parts by mass of MDI, 2 parts by mass of polymeric MDI, and 3 parts by mass of HDI nurate were added, and the temperature was raised to 110°C. The mixture was reacted for about 3 hours until the isocyanate group content became constant, and then reacted at 100°C for about 3 hours under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a urethane prepolymer. The NCO / OH ratio during production of the resulting urethane prepolymer was 2.30, and the NCO% of the urethane prepolymer was 2.29% by mass. Using this urethane prepolymer, a decorative board was obtained in the same manner as in Example 1.

[0064] [Comparative Example 1] A four-neck flask equipped with a stirrer, thermometer, inert gas inlet, and reflux condenser was charged with 30 parts by mass of crystalline PEs-2, 10 parts by mass of crystalline PEs-3, 30 parts by mass of crystalline PEs-4, 10 parts by mass of other PEs-1, and 2 parts by mass of PEt-1, and heated under reduced pressure at 90°C to dehydrate until the moisture content was 0.05% by mass or less. Next, after cooling the temperature in the reaction vessel to 60°C, 18 parts of MDI was added, and the temperature was raised to 110°C. The mixture was reacted for about 3 hours until the isocyanate group content became constant, to obtain a urethane prepolymer having an isocyanate group. The NCO / OH ratio at the time of producing the obtained urethane prepolymer was 2.77, and the NCO% of the urethane prepolymer was 3.86% by mass. Using this urethane prepolymer, a decorative board was obtained in the same manner as in Example 1.

[0065] [Method for measuring number average molecular weight] The number average molecular weights of the polyols used in the examples and comparative examples are values ​​measured by gel permeation chromatography (GPC) under the following conditions.

[0066] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 0.4% by mass in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following standard polystyrene.

[0067] (Standard polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0068] [Method of measuring the melting point of crystalline polyester polyol] 10 mg of each crystalline polyester polyol was weighed into a measurement container, and using a differential scanning calorimeter ("DSC 220C" manufactured by Seiko Electronics Co., Ltd.), the temperature was raised from 20°C to 210°C at a nitrogen gas flow rate of 50 ml / min and a heating rate of 10°C / min, and then held at 210°C for 3 minutes, after which the temperature was lowered to -100°C at a cooling rate of 50°C / min, and a second heating was performed again to 200°C, and the melting point (°C) was determined from the DSC curve drawn on a chart.

[0069] [Method of evaluating adhesion] The adhesion was evaluated by the following two methods.

[0070] <3D molding test> The decorative plate prepared by the above method was aged at 23° C. for 5 days, after which the side surface and the cross section of the groove were observed to evaluate the 3D formability. "◯": No lifting of the decorative sheet was observed. "Δ": Some lifting of the decorative sheet was observed, but was at a level that did not pose a problem in practical use. "X": Adhesion was not possible.

[0071] <Creep test> The urethane prepolymers obtained in the examples and comparative examples were melted at a temperature of 120°C for 1 hour. The adhesive was applied to a polyethylene terephthalate sheet using an applicator so that the thickness was 50 μm. The adhesive was left at 23°C for 15 minutes, and then left at 80°C for 2 minutes. MDF (medium density fiberboard) was attached to the applied layer and pressed with a pressing roller. After pressing, a load of 75 g was applied to a 25 mm wide test piece in a 90° direction, and the peel length (mm) of the polyethylene terephthalate sheet after 15 minutes was measured and evaluated as follows. "◯": The peeling length was 2 mm or less. "△": The peeling length was more than 2 mm and 10 mm or less. "X": The peeled length exceeded 10 mm or the weight fell.

[0072] [Table 1]

[0073] [Table 2]

[0074] It was found that the decorative board of the present invention has excellent initial adhesion between the substrate and the decorative sheet, and also has excellent final adhesion with no lifting or peeling of the decorative sheet from the grooved substrate.

[0075] On the other hand, Comparative Example 1 is an embodiment in which the crystalline polyester polyol (a1-1) was not used, and the adhesiveness was poor.

Claims

[Claim 1] A method for manufacturing a decorative sheet in which a substrate and a decorative sheet are bonded together via an adhesive, comprising the steps of: A decorative sheet is continuously bonded to the side surface and the flat surface of the substrate, The adhesive is A moisture-curable polyurethane hot melt adhesive containing a urethane prepolymer having an isocyanate group, which is a reaction product of a polyol (a) and a polyisocyanate (b), The polyol (a) is The composition contains a crystalline polyester polyol (a1-1) having a melting point of more than 80° C. and not more than 140° C., and the amount of the crystalline polyester polyol (a1-1) used is in the range of 5 to 45 parts by mass per 100 parts by mass of the total of the polyol (a) and the polyisocyanate (b), The polyol (a) further contains a crystalline polyester polyol (a1-2) having a melting point of 40 to 80° C., the crystalline polyester polyol (a1-2) contains a product obtained by reacting hexanediol with dodecanedicarboxylic acid, and a polycaprolactone polyol; the total amount of the crystalline polyester polyols (a1-1) and (a1-2) used is 50 parts by mass or more per 100 parts by mass of the total amount of the polyol (a) and the polyisocyanate (b); the polyol (a) further contains a polyester polyol (a1-3) other than the polyols (a1-1) and (a1-2); the molar ratio [NCO / OH] of the hydroxyl group of the polyol (a) to the isocyanate group of the polyisocyanate (b) is in the range of 1.5 to 5; The polyisocyanate (b) contains a diisocyanate (b-1), an isocyanurate compound (b-2), and / or a polymethylene polyphenyl polyisocyanate (b-3), A method for producing a decorative board, characterized in that the decorative board is obtained by vacuum wrapping molding.

Citation Information

Patent Citations

  • Decorative film, decorative film molded product obtained by molding decorative film and decorative sheet obtained by laminating decorative film

    JP2004074657A

  • Moisture-curable polyurethane hot melt adhesive and decorative finishing member

    JP2013087150A

  • Moisture-curable polyurethane hot melt resin composition and decorative fixture member

    JP2014196411A

  • Moisture-curable polyurethane hot-melt composition

    JP2018070684A

Cited By

  • Polycyclic aromatic compound

    KR1020240012318A

  • Polycyclic aromatic compound

    KR1020250003333A

  • Polycyclic aromatic compound

    KR1020250003347A

  • Polycyclic aromatic compound

    KR1020250003359A

  • Polycyclic aromatic compound

    KR1020250124034A